Strategies Employed by The Main Character (Jodi) in Responding Impoliteness of Others in “Tall Girl” Movie (2019): A Socio-Pragmatic Studies - Yahya Krisetya; Widhiyanto; Suwandi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This research investigated how impoliteness strategies and responses were portrayed through Jodi, the main character in the movie Tall Girl (2019). Impoliteness is a part of sociopragmatics because it relates to the social context. Socio-pragmatics can be interpreted as the study of the meaning of speech related to social aspects that cover culture and society, language, social situations, and social classes. This descriptive qualitative analysis identified 24 utterances of impoliteness received by Jodi, which were divided into 6 utterances of bald on record, 6 utterances of positive impoliteness, 6 utterances of negative impoliteness, 5 utterances of sarcasm or mock politeness, and 1 withheld politeness utterance. These utterances most frequently targeted her physical height. In response to impoliteness’s utterances, Jodi employed a range of strategies: at first silence and avoidance, later humour and topic-shifting, and ultimately direct confrontation. This progression illustrated her psychological growth and shifting social power toward confidence and self-acceptance. The whole story in the movie related to the real life of students’ interactions in the school environment. The analysis also highlights the educational value of the movie. The research identified eleven moral values, including bravery, humility, sincerity, trustworthiness, and kindness. These values, demonstrated not only by Jodi but also by her friends and family, reinforce the importance of mutual respect, resilience, and self-acceptance. Overall, the findings suggested that the movie Tall Girl (2019) presents impoliteness both as a realistic reflection of impolite things in social interaction. At the same time, it offered valuable moral lessons that can be learned by the teachers and students in socio-pragmatics fields.